Narrative inquiry on breast cancer patients in times of covid-19 pandemic - Danganan-Castillo, Rachel (Indonesian Journal of Health Science, 2024)
In the Philippines, there is a substantial quantity of research on the experience of breast cancer patients under treatment, but little is known about those patients who had difficulty making sense of and understanding their experiences after the delivery of medication before and even during the pandemic. Hence, this research documented the personal narratives of female breast cancer patients in the province of Bataan highlighting their experiences in undergoing treatment before and during the COVID19 pandemic. The wider objective of the study is enhancing the support that can be offered to women with breast cancer by embracing the process of meaning-making. By using a narrative framework, an unstructured narrative encounter with 8 women diagnosed with Stage I-II breast cancer who completed their curative treatment 6-47 months prior to the interview were conducted. The oral stories of these women were transcribed and retold into a prose account which were then analyzed using narrative analysis. While undergoing treatment before the pandemic, the cancer patients were living through physical pain, enduring a roller coaster of emotions, going through spiritual awakening, building a strong support system and engaging in a healthy diet and lifestyle. During the pandemic, they are faced with the rising cost of healthcare services, increasing risk of COVID19 infection and missing routine check-ups due to strict health protocols. It is recommended that they should be given access to professional psychological and social support and improved nutritional support programs which will be offered through online or offline modalities by the healthcare institutions or the Department of Health and its instrumentalities. Through the course of the pandemic, healthcare institutions should expand their teleconsultation program which will cover a wider range of oncologic services that will be made available to cancer patients. Virtual visits may be permanently adopted and healthcare institutions should look into formalizing a breast screening programs that operate in parallel to primary care.